The Perception of Emerging Cattle Farmers on Extension and Advisory Services in Improving the Welfare of Cattle in Sinthumule-Kutama Areas of Makhado Municipality, Vhembe District, Limpopo Province, South Africa - Muano Thononda; Elliot Mahlengule Zwane; Ernet Modibe Letsoalo (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2024)
Livestock farmers in the Limpopo Province benefitted from the land reform projects. This led to an increase in the number of emerging cattle farmers who desired to move from small-scale to commercial cattle farming. These emerging cattle farmers had high expectations for government support through extension and advisory services to improve the welfare of their cattle. However, the study aimed to investigate the perceptions of 80 emerging cattle farmers concerning the importance of agricultural extension and the impact of extension advisors in improving the welfare of their cattle. The study was conducted in 18 villages of the Sinthumule-Kutama areas under Makhado Municipality. The study used quantitative and qualitative methods and simple random sampling. Questionnaires were used to collect primary data. The Statistical Package for Social Sciences (SPSS) tool was used for analysis, and the mean score was produced to address the study’s objectives. The results indicated that farmers agreed on the importance of cattle welfare and that they are knowledgeable about it, and methods used by extension workers are essential. Furthermore, they decided that the extension activities contribute to their knowledge of cattle welfare. The paper concludes by making the following recommendations. Extension workers should collaborate with some of the farmers who are leaders within the community to manage cattle welfare when extension workers are not around. Cattle farmers of Sinthumule-Kutama are expected to be trained on livestock welfare.